Dentin Hypersensitivity: A Literature Review - Gustantyo Wahyu Wibowo; How Kim Chuan; Susanna Halim (Jurnal Penelitian Pendidikan IPA, 2025)
Dentin hypersensitivity is characterized by brief, intense pain triggered by external stimuli that affect exposed dentin with open tubules. The condition is primarily caused by two factors: the exposure and loss of dentin and the opening of dentin tubules, which allows sensory signals from the pulp to be transmitted in response to stimulation of the dentin surface. A precise diagnosis is crucial before initiating treatment and begins with a thorough patient medical history and clinical examination. Various treatment options have been developed to manage sensitivity, focusing primarily on nerve desensitization and the closure of open dentinal tubules. Developing a better understanding of the causes and mechanisms of dentin hypersensitivity is essential for effective prevention and treatment strategies for patients suffering from this condition. This review aims to provide dental professionals with comprehensive knowledge about dentin hypersensitivity, including its causes, diagnostic procedures, clinical management techniques, and innovative methods for reducing sensitivity.